Analysis of delays in a channel depending on its quality - Ткаліч, О. П.; Нечипорук, О. П.; Андрухович, П. О.; Таран, Є. С.; Бліновська, М. Л. (Problems of Informatization and Management, 2010)
The article devoted to the analysis of delays in the communication channel depending on its quality, using a utility ping. Conducting this analysis allowed us to research how to use utility ping, which is standard on all operating systems and the supply of network equipment, as well as the implementation of a simple control integrity into the communication channel